2018
DOI: 10.3390/land7010026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding System on Enteric Methane Emissions from Individual Dairy Cows on Commercial Farms

Abstract: This study investigated the effects of feeding system on diurnal enteric methane (CH 4 ) emissions from individual cows on commercial farms. Data were obtained from 830 cows across 12 farms, and data collated included production records, CH 4 measurements (in the breath of cows using CH 4 analysers at robotic milking stations for at least seven days) and diet composition. Cows received either a partial mixed ration (PMR) or a PMR with grazing. A linear mixed model was used to describe variation in CH 4 emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Limiting the amount of CH 4 released from metabolic transformations and adaptation of suitable measurement techniques continue to pose problems for researchers [1,[3][4][5][6][7]. In a study by Eckert et al [8], the CH 4 emission rate estimated at milking stations was similar to that observed in cows in respiratory chambers. It was determined that owing to further validation of the method, monitoring of CH 4 emissions on the farm during milking can provide an inexpensive and reliable method for estimating daily CH 4 production by individual dairy cows.…”
Section: Introductionmentioning
confidence: 91%
“…Limiting the amount of CH 4 released from metabolic transformations and adaptation of suitable measurement techniques continue to pose problems for researchers [1,[3][4][5][6][7]. In a study by Eckert et al [8], the CH 4 emission rate estimated at milking stations was similar to that observed in cows in respiratory chambers. It was determined that owing to further validation of the method, monitoring of CH 4 emissions on the farm during milking can provide an inexpensive and reliable method for estimating daily CH 4 production by individual dairy cows.…”
Section: Introductionmentioning
confidence: 91%